2016
DOI: 10.1039/c5cc06955f
|View full text |Cite
|
Sign up to set email alerts
|

Chemical processing of three-dimensional graphene networks on transparent conducting electrodes for depleted-heterojunction quantum dot solar cells

Abstract: We present a novel chemical procedure to prepare three-dimensional graphene networks (3DGNs) as a transparent conductive film to enhance the photovoltaic performance of PbS quantum-dot (QD) solar cells. It is shown that 3DGN electrodes enhance electron extraction, yielding a 30% improvement in performance compared with the conventional device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 20 publications
2
35
0
Order By: Relevance
“…1) the formation of ZnOC bonds after chemisorption of Zn 2+ ions on the surface of the embryonic ZnO QDs and reaction with GO functional groups, and 2) the reaction of Zn 2+ ions with GO to establish ZnO bonds and combine with embryonic ZnO QDs. The layer‐by‐layer chemical exfoliation process of GO nanosheets occurs during these reactions and ZnO QDs are wrapped with rGO as a hybrid structure …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) the formation of ZnOC bonds after chemisorption of Zn 2+ ions on the surface of the embryonic ZnO QDs and reaction with GO functional groups, and 2) the reaction of Zn 2+ ions with GO to establish ZnO bonds and combine with embryonic ZnO QDs. The layer‐by‐layer chemical exfoliation process of GO nanosheets occurs during these reactions and ZnO QDs are wrapped with rGO as a hybrid structure …”
Section: Resultsmentioning
confidence: 99%
“…In these hybrid nanostructures, graphene is an efficient and fast charge extraction layer . In our previous works, we fabricated hybrid nanostructures of PbS quantum dots (QDs) and graphene and employed them as an absorber layer in quantum dot solar cells and improved the performance of the device by up to 40% . Wang et al also demonstrated that the hybrid nanostructure of graphene and TiO 2 NPs can improve the device performance of a perovskite solar cell up to 15.6%.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, nanostructures can not only improve optical absorption, but also simultaneously shorten the photo-generated carrier collection length and result in more effective carrier collection. [33][34][35][36] Radial p-n junctions and nanostructured electrodes, in particular, have been proven effective for the aforementioned purposes. Nonetheless, much literature has reported that the proper design of solar energy harvesting devices is of utmost importance and optimizations of different key aspects are needed.…”
Section: Introductionmentioning
confidence: 99%
“…28 Graphene (Gr), a single-layer of carbon sheet, exhibits excellent electronic conductivity [29][30][31] and optical transmittance [32][33][34] with great potential to replace metals as transparent electrodes. [35][36][37][38][39][40][41][42] Gr/Si structures have been studied in solar cells, 36,38,39 as well as, visible and INR photodetectors, 41,[43][44][45][46][47][48] showing excellent performances. Ultra-shallow (essentially, zero X J ) Gr/Si Schottky structure could be more suitable for UV detection, because it not only resolves the serious surface recombination due to the shallow junction satisfying the UV light penetration depth in Si, but also simplifies the fabrication process to reduce the cost.…”
Section: Introductionmentioning
confidence: 99%